Toward A Taxonomy of Multidimensional Constructs - Law, Kenneth S.; Wong, Chi‐Sum; Mobley, William M. (Academy of Management Review, 1998)
We propose a taxonomy of multidimensional constructs based on the relations between the construct and its dimensions. Multidimensional constructs that exist at deeper levels than their dimensions we term latent model. We call constructs formed as algebraic functions of their dimensions aggregate model, whereas constructs formed as different profiles of dimensional characteristics we term profile model. We discuss the nature of multidimensional constructs defined under these models and their operationalizations in empirical research.